Administration of GnRH at day 20 of AI and embryonic losses in synchronized crossbred buffalo - Abulaiti, Adili; Naseer, Zahid; Liu, Wenju; Ahmed, Zulfiqar; Abdelrahman, Mohamed; Shaukat, Aftab; Pang, Xunsheng; Wang, Shujuan (Frontiers in Veterinary Science, 2023)
Introduction Following the application of different artificial insemination and synchronization protocols, the synchronized buffaloes had a higher incidence of early embryonic or fetal death, thus impairing reproductive performance. Therefore, there is a need to devise a synchronizing program that can improve conception, allow early pregnancy diagnosis, reduce early embryonic losses, and provide an early clue for pregnancy diagnosis and establishment. The present study aimed (1) to determine the effect of administration of different GnRH doses at day 20 of artificial insemination (AI) on the reproductive performance of buffaloes and (2) to observe the influence of synchronization protocol, parity, age, milk production, and body condition score (BCS) on early embryonic loss and progesterone (P4) levels in crossbred buffaloes. Methods Crossbred buffaloes (n = 101) were synchronized using the GPGMH protocol. At day 20 of AI, the synchronized buffaloes were randomly divided into four groups and administrated GnRH doses (0, 100, 150, and 200 μg). The buffaloes were monitored for ovarian dynamics, P4 level, non-return rate, embryonic/fetal losses, and pregnancy rates. The previously synchronized buffaloes were also classified for synchronization protocol (with or without GnRH), parity (nulli- or multiparous), milk production (high or low), BCS (low, medium, or good) or age (>3 or < 3 years) groups for observing the embryonic loss and P4 level variations. Results The results indicated no difference (P > 0.05) in CL size, P4 level, pregnancy rate and embryo/fetal losses across the treatment groups at different observation periods. There was a high (P < 0.05) incidence of early embryonic mortality in aged, multiparous, low BCS and low milk-producing buffaloes treated without GnRH. Conclusion The data suggest that GnRH 200 μg at day 20 of AI improves embryo survival and pregnancy maintenance in crossbred buffaloes.